Nutrition & Child Care: A Practical Guide - Ghosh Shanti; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2004)
This book primarily deals with the child care. The key to child's health is a healthy mother and balanced nutritional practices. Reasons like pregnancy at younger age and malnutrition highly affect hemoglobin count, increasing the risk of giving birth of a low weight or anemic baby. High Prevalence of anemia causes reduction in hemoglobin level of less than 11 points. Though the best food that can be given to the child by mother is the breast milk, infant feeding practices remain as unsatisfactory as ever. The median duration of exclusive breastfeeding is about three months in urban areas and a little more in the rural areas. Complementary feeding plays important role in the growth of children. Nutritional food is one of the main factors of the healthy growth, and from the age of 3 to 5 years, it is even more significant. Immunization coverage has had a setback but is now catching up again. A great deal of effort is going into eliminating poliomyelitis and four or more immunization rounds are held in a year. However, laudable the aim of eliminating polio, this interferes with the normal health delivery program for mothers and children including immunization. And this book also explains how health and nutritional educations can be achieved among the communities.
Keywords: Nutrition and Dietetics,Pediatrics; Electronic books